2017
DOI: 10.1007/s12098-017-2333-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound is Comparable with Chest Roentgenogram for Diagnosis of Community-Acquired Pneumonia in Hospitalised Children

Abstract: LUS can be considered to be used first before radiography in children with suspected CAP. This will reduce the exposure of radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…From this set of articles, 99 (12.6%) abstracts were identified for further analysis based on PRISMA analysis (Figure ). QUADAS review was applied to the 99 articles and 12 (1.5%) (Table ) were selected for inclusion in the meta‐analysis based on inclusion criteria, data collection, and lack of bias. All studies were observational.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From this set of articles, 99 (12.6%) abstracts were identified for further analysis based on PRISMA analysis (Figure ). QUADAS review was applied to the 99 articles and 12 (1.5%) (Table ) were selected for inclusion in the meta‐analysis based on inclusion criteria, data collection, and lack of bias. All studies were observational.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not specify sonographer experience. One study included only novice radiologist sonographers following 4 h of LUS training and performance of 15 LUS exams . One study evaluated both expert and novice pediatric emergency medicine sonographers, with novice being defined as fewer than 25 LUS exams .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that pediatric lung US can be performed quickly. Performance times of 2 to 15 minutes for radiologists and 4 to 10 minutes for nonradiologist clinicians have been reported. Our study found a mean time of 2.9 (SD, 1.4) minutes to perform the point‐of‐care lung US examinations.…”
Section: Discussionmentioning
confidence: 99%